Japanese Access to Mexico: The Structure of the Japan-Mexico FTA - Pezzola, Anthony A. (México y la Cuenca del Pacífico, 2017)
The political forces behind trade negotiations extend far beyond a few specific industries or products. Delaying the liberalization of specific products within free trade agreements (FTAs) provides policymakers with an important means of garnering support for ftas; however, the specific characteristics of industries that allow them to obtain this preferential treatment remain unclear. The analyses of Mexico’s tariff reduction schedule (TRS) within the Japan-Mexico FTA demonstrates that subnational constituent interests directly influence which industries policymakers chose to protect. As such, the economic interests of geographically specific electoral districts influenced the design and ratification of the FTA and Mexico’s integration into the global market.